Analisa Sistem Pendukung Keputusan Untuk Menentukan Prioritas Strategi Terbaik Sebagai Upaya Penguatan Inovasi Teknologi Dalam Negeri Ina Tews BPPT - Utomo, Satrio (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
INA TEWS (Indonesian Tsunami Early Warning System) is an important part of the national disaster mitigation system, and a domestic technological innovation for tsunami disaster mitigation. In the assessment of technology development priorities, INA TEWS uses the Analytical Hierarchy Process (AHP) method and the Technology Readiness Level (TRL) method to assess the level of technology readiness. There are four criteria of assesment, namely urgency of need, financing, supply of raw materials, and acceleration of innovation. INA TEWS technology is divided into four technology components, namely Technoware, Humanware, Infoware, Orgaware. Based on the preferences of expert respondents, it shows that the most prioritized criteria at this time are supply of raw materials (30.9%), urgency of need (28.4%), financing (22%) and the last is innovation creation (18.8%). For the highest priority technology components are Technoware (42.5%), Orgaware (28.4%), Humanware (19%), and finally Infoware (10.1%). Technoware components are priority and top. As seen from the test results of various sensitivity chart analysts, the Infoware component looks the lowest of all other technology components. It seems that Infoware has not become the focus of attention for management in developing INA TEWS. For this reason, the Infoware component is encouraged to immediately meet the aspect of innovation creation criteria.